Network Security Assessment Using Internal Network Penetration Testing Methodology - Deni Satria; Alde Alanda; Aldo Erianda; Deddy Prayama (JOIV : International Journal on Informatics Visualization, 2018)
The development of information technology is a new challenge for computer network security systems and the information contained in it, the level of awareness of the importance of network security systems is still very low. according to a survey conducted by Symantec, the desire to renew an existing security system within a year within a company has the result that only 13% of respondents consider changes to the security system to be important from a total of 3,300 companies worldwide as respondents. This lack of awareness results in the emergence of security holes that can be used by crackers to enter and disrupt the stability of the system. Every year cyber attacks increase significantly, so that every year there is a need to improve the security of the existing system. Based on that, a method is needed to periodically assess system and network security by using penetrarion testing methods to obtain any vulnerabilities that exist on the network and on a system so as to increase security and minimize theft or loss of important data. Testing is carried out by using internal network penetration testing method which tests using 5 types of attacks. From the results of the tests, each system has a security risk of 20-80%. From the results of these tests it can be concluded that each system has a security vulnerability that can be attacked.